ICAANE Wien Proceedings 2016, Vol. 1 - Horejs, Barbara (Harrassowitz Verlag, 2018)
Cover -- Title Pages -- Imprint -- Contents -- B. Horejs: Foreword to the 10th ICAANE Proceedings -- Vienna Statement: Statement about the Threat to Cultural Heritage in the Near East and North Africa -- K. O. Sotiriou: New Insights into the Illicit Antiquities Trade in the Eastern Mediterranean -- TRANSFORMATION & MIGRATION (edited by B. Horejs and Ch. Schwall) -- K. Nagaya - S. Fujii: Revival of Lithic Technology in Badia: New Insights from the Pre-Pottery Neolithic B Outpost of Wadi Abu Tulayha, Southern Jordan -- A. Mączyńska: Is There a Place for Prehistoric Egypt in Near Eastern Archaeology? Some Remarks on Early Relations between Egypt and its Neighbours -- Ch. Schwall - B. Horejs: Permanent or Seasonal? Evidence of Settlements in Late Chalcolithic Western Anatolia -- S. Di Paolo: Central Zagros. Cultural Contacts between Mesopotamia and Iran in the Old Babylonian Period -- A. Alizadeh: The Emergence of Political Buffer Zones on the Eve of Early States in Southwestern Iran -- M. D'Andrea: The EB-MB Transition in the Southern Levant: Contacts, Connectivity and Transformations -- J. M. Martín García - M. Artzy: Cultural Transformations Shaping the End of the Late Bronze Age in the Levant -- M. Montesanto: Evidence of Transformation: The Early Iron Age Aegeanizing Pottery Assemblage at Alalakh -- J. Bessenay-Prolonge - R. Vallet: From Bronze Age to Iron Age in the Northeast Iran: The Case of Tureng Tepe -- T. Koizumi - H. Ojima - H. Yoshida - A. Yoshida: A Pyrotechnological Study of Ubaid and Late Chalcolithic Pottery: Estimated Firing Temperatures -- Sh. Shabo: Late Bronze Age Pottery from Qatna and ist Surrounding Region: Typological and Petrographical Approaches -- A. Passerini - E. Rova - E. Boaretto: Revising the Absolute Chronology of the 4th and 3rd Millennia BCE in the Southern Caucasus.